Website usability and purchase intention among generation z users in fashion e-commerce: the mediating role of user satisfaction - Anita Safitri (Institute of Computer Science (IOCS), 2026)
This study examines the relationship between website usability and purchase intention within the population of Generation Z consumers engaged with fashion e-commerce platforms, with user satisfaction as a mediating variable. A quantitative approach was employed using a survey of 198 Generation Z users with experience in fashion e-commerce. Website usability was measured using the WEBUSE framework, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings demonstrate that navigation and links, as well as user interface design, have significant positive effects on both user satisfaction and purchase intention. In contrast, content, organization and readability, and performance and effectiveness do not have significant effects. Furthermore, user satisfaction does not significantly influence purchase intention, indicating that Generation Z users may place greater emphasis on specific usability features than overall satisfaction in making purchase decisions. Mediation analysis reveals that user satisfaction has a limited mediating role. These findings highlight the importance of optimizing navigation and interface design to enhance user experience and increase purchase intention. This study contributes to the literature by showing that purchase intention among Generation Z is more strongly influenced by specific usability dimensions than overall satisfaction